2022
DOI: 10.1097/qai.0000000000003016
|View full text |Cite
|
Sign up to set email alerts
|

Associative Prediction of Carotid Artery Plaques Based on Ultrasound Strain Imaging and Cardiovascular Risk Factors in People Living With HIV and Age-Matched Control Subjects of the CHACS Cohort

Abstract: for the Canadian HIV and Aging Cohort StudyBackground: There is a need for a specific atherosclerotic risk assessment for people living with HIV (PLWH).Setting: A machine learning classification model was applied to PLWH and control subjects with low-to-intermediate cardiovascular risks to identify associative predictors of diagnosed carotid artery plaques. Associations with plaques were made using strain elastography in normal sections of the common carotid artery and traditional cardiovascular risk factors.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Their data showed that HIV-positive people in Switzerland had a similar degree of non-calcified/mixed plaque and high-risk plaque and may have less calcified coronary plaque and lower coronary atherosclerosis involvement and severity score than HIV-negative people with similar Framingham risk scores. In contrast to this study, in a recent Canadian work, the authors evaluated 102 PLWH and 84 controls who performed ultrasound scans of the left and right common carotid arteries and internal carotid arteries [19]. The authors concluded that HIV status has been identified as a cofactor associated with carotid artery plaques.…”
Section: Discussionmentioning
confidence: 75%
“…Their data showed that HIV-positive people in Switzerland had a similar degree of non-calcified/mixed plaque and high-risk plaque and may have less calcified coronary plaque and lower coronary atherosclerosis involvement and severity score than HIV-negative people with similar Framingham risk scores. In contrast to this study, in a recent Canadian work, the authors evaluated 102 PLWH and 84 controls who performed ultrasound scans of the left and right common carotid arteries and internal carotid arteries [19]. The authors concluded that HIV status has been identified as a cofactor associated with carotid artery plaques.…”
Section: Discussionmentioning
confidence: 75%